STRATEGI PROGRAM STUDI MEWUJUDKAN LEARNING OUTCOME - Arifin Suking; Sitti Roskina Mas; Fikram Anis (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2022)
This study aims to determine: (1) adjustment of study program learning outcomes, and (2) study program strategies to realize learning outcomes. This study uses a quantitative approach with explanatory descriptive type. The subjects of this study were 15 lecturers. Data collection techniques using questionnaires, interviews, and documentation. The data analysis technique used is descriptive analysis technique using the percentage formula. The results of the study show that: (1) the adjustment of learning outcomes is in the good category, because it refers to the KKNI which is used as a reference in the assessment; and (2) the study program strategy to achieve learning outcomes is in the good category, through integration strategies in learning, alumni involvement, and curriculum adjustments.